Outcome of autologous bone marrow transplant in patients with relapsed and refractory diffuse large B-cell lymphoma in relation with prognostic factor: A single-center experience - Fawaz Salim Yousif; Bassam Francis Matti; Zina Ali Al-Bakri; Safa A. Faraj; Mazin A. Mohammed; Zahraa S. Shakir; Mahmood W. Khalid; Saba H. Al Hlali; Sarah M. Saeb; Kareem K. Khanjar; Maryam R. Humadi (Iraqi Journal of Hematology)
BACKGROUND: Currently, about 50% of diffuse large B-cell lymphoma patients are relapsed following their complete response to first-line therapy. The treatment strategy for fit patients with relapsed refractory diffuse large B-cell lymphoma (R/R DLBCL) has been done with salvage therapy with non-cross resistant combination chemo-immunotherapy regimens followed by high-dose chemotherapy and autologous stem cell transplantation (ASCT). OBJECTIVES: The aim of study was to evaluate the outcome of ASCT for R/R DLBCL in relation to certain prognostic parameters. PATIENTS, MATERIALS AND METHODS: This is retrospective study, conducted from May 2014 to December 2022, at Hematology and BMT Center of Medical City Complex in Baghdad. Thirty-six patients with R/R DLBCL were investigated pre- and post-ASCT; the recorded data included patient disease status pre-transplant, early mortality rate, and type of response at day 100 post-transplant and, survival rate, relapsed rate, and mortality at the end of the study were documented accordingly. RESULTS: The mean age of DLBCL patients in this study was 41.3 (14–65) years, post-ASCT at day 100; there were 33 (91.6%), 2 (5.5%), and 1 (2.7%) patients in complete remission, relapsed progressive disease, and death, respectively, At 3-year posttransplant, the overall survival (OS) was 71%, whereas the event-free survival (EFS) was 59%. According to disease status pre-ASCT, the OS was 62%, 80%, and 66% with P = 0.7, whereas the EFS was 66%, 60%, and 50% with P = 0.5 for CR, UCR, and PR, respectively. CONCLUSION: Iraqi bone marrow transplant center data showed acceptable OS and EFS results in the treatment of R/R DLBCL patients in areas where there is no more option in terms of better OS and EFS but with insignificant relation to the available prognostic factor.